Suspected adipose tumours of the hand and the potential risk for malignant transformation to sarcoma: a series of 14 patients - Leclère, Franck Marie Patrick; Casoli, Vincent; Pelissier, Philippe; Vogt, Peter M.; Desnouveaux, Emilie; Spies, Christian; Weigert, Romain; Choughri, Hussein (Archives of orthopaedic and trauma surgery, 2015)
Lipomas are associated with a variety of symptoms including neuropathies, local compression of the surrounding tissues, aesthetic complaints and may be graded as liposarcomas histologically. This study was performed to review our surgical management at the level of the hand.